Effect of Different Weed Management Practices on Weed Dynamics, Growth and Yield of Maize (Zea Mays L.) in Lalitpur, Nepal - Karki, Jiwan Bahadur; Giri, Homnath (Agronomy Journal of Nepal, 2025)
A field experiment was conducted in Godawari municipality-11, Tahakhel, Lalitpur, Nepal during April to August, 2024 to evaluate the effect of different weed management practices on weed dynamics, growth and yield of maize. The experiment was carried out in randomized complete block design (RCBD) comprising of seven treatments with three replications. Mankamana-4 maize variety was used in the experiment. Data on crop growth, weed dynamics and yields were recorded and analyzed. The data tabulation was done in MS-EXCEL and analysis of data was done by using R. The experiment results revealed application of atrazine 50% WP @1kg a.i/ha as Pre emergence (PE) treatment resulted in highest grain yield (7.35 mt/ha) which was statistically at par with the treatment pendimethalin 30% EC @0.5 kg a.i/ha + atrazine 50% WP @0.5 kg a.i/ha as PE (7.31 mt/ha) and followed by the hoeing at 25 DAS (7.17 mt/ha).Different weed species belonging to 8 families were identified. The total weed density and weed dry weight were found significantly (p